Evolving ideas on non-alcoholic fatty liver disease: from risk to catastrophe - Yu. M. Stepanov; O. Yu. Filippova (Zaporožskij Medicinskij Žurnal)
The aim of the work is to study the development of non-alcoholic fatty liver disease (NAFLD) accompanied by changes in the clinical course and general transformation of diagnostic and therapeutic approaches to a patient with comorbid conditions.